The Role of Lead and Molybdenum and Their Effects on Oxidative Stress in Ruminant Animals: Subject Review - Palani, Zirak M R; Ameen, Gulala W; Shekhani, Dawod Noori M (Nabatia, 2025)
Ruminant animals have significantly improved global food security, particularly in rural and semi-arid lands, where milk, meat, and wool are food producers, among other items. Their production and health may be altered by several environmental conditions. There is also critical exposure to heavy metals and trace elements. Oxidative stress is an important biological process that links environmental pollution to reduced physiological actions. The imbalance between reactive complimentary radicals and antioxidants causes cellular damage to essential tissues lowering growth and condition, affecting immune functions, and reducing ruminant reproductive efficiency. Lead increases reactive oxygen species production while reducing antioxidant enzymes superoxide dismutase and catalyze effectiveness, increasing the formation of several oxidative stress markers, including malondialdehyde. Molybdenum, however, is a trace element that helps activate several important enzymes in this study, including sulfur and purine metabolism aggravation. With a protective potential, it can have a dual role in oxidative stress: a beneficial for ruminant animals when applied the recommended doses and degradation: it can help and compromise other minerals while provided unreasonably. It analysis recent original research on the performance of ruminants based on current high-level research evidence concerning lead and molybdenum. Further, I will explain a physiological concept, groundbreaking research, and expert views to offer an explanation of how these two elements work and influence their oxidative balance in ruminants.